EFEKTIVITAS METODE DEMONSTRASI TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN ALAT DAN MESIN PERTANIAN SISWA KELAS X SMK NEGERI 6 TAKALAR - Fajarudin, Fajarudi; Rukma, Ady; Kadirman, Kadirman (Jurnal Pendidikan Teknologi Pertanian, 2017)
This research aims to determine the effectiveness of the  demonstration methods on the subjects of agricultural tools and machines class X Plantations Agribusiness of SMK Negeri 6 Takalar. This research is quasi experiment in  pre-test and post-test form with number of population is 21 people and all the population is used to be sample. Data obtained by documentation technique, testing, and observation. Research procedure includes stages: pre-test, treatment, post-test. The results of the research showed that the application of the demonstration learning methods is effective and can increase student achievement in subjects agricultural tools and machines of class X ATP of SMK Negeri 6 Takalar, Takalar district. This was evident in the pre-test and post-testt which  increased. Based on the quantitative analysis of this research showed that the classical learning completeness in the pre-test about 14.28%, on a post-test increased to 90.48% with the effectiveness level of learning demonstration methods stood at 80.73 a scale of 100